Cardio-Hematology Crossroads: A Diffuse Large B-Cell Lymphoma Case Presenting with a Cardiac Mass - Tunçil, Pınar; Yiğit, Zeynep Sebla; Çınar, Olgu Erkin; Kaynar, Leylagül (The European Research Journal, 2026)
Cardiac involvement by diffuse large B-cell lymphoma (DLBCL) is a rare clinical entity that often presents with nonspecific symptoms, making early diagnosis particularly challenging. In this context, we report a case that highlights the diagnostic obstacles and the importance of early evaluation. A 58-year-old male presented with dyspnea, malaise, fingertip numbness, weight loss, and shoulder pain. Transthoracic echocardiography revealed a right atrial mass, prompting further assessment. Positron Emission Tomography-Computed Tomography demonstrated increased 18F-FDG (18F-fluorodeoxyglucose) uptake in multiple regions, including the cardiac musculature, raising suspicion for disseminated lymphoproliferative disease. The biopsy of the left superior cervical lymph node confirmed diffuse large B-cell lymphoma. The patient underwent six cycles of chemoimmunotherapy and achieved complete metabolic remission. This case underscores the need to consider lymphoid malignancies in the differential diagnosis of intracardiac masses and persistent cardiac symptoms without an obvious cause. Early use of multimodal imaging and prompt histopathological confirmation are critical for accurate diagnosis and appropriate treatment planning. Rapid initiation of immunochemotherapy may improve clinical outcomes and reduce the risk of severe cardiac complications.